Total Quality Management and Innovation Performance: An Empirical Evaluation of Quality and Innovation in Dubai Islamic Bank Pakistan - Sarwar, Huma (Advances in Social Sciences Research Journal, 2017)
The empirical study seeks to investigate the relationship between total quality management practices and organizational quality and innovation performance of Dubai Islamic Bank, Pakistan Dubai Islamic Bank, Pakistan. The current research study adapted the scale from previous studies and the data will be collected through self-administered questionnaires from managerial/administrative staff Dubai Islamic Bank, Pakistan. This research work contributed to the TQM literature with understanding of the relationship between TQM practices and banking organization’s quality and innovation performance, which reveals some crucial guidelines for the senior management of the Dubai Islamic Bank, Pakistan to modify the current implementation process of TQM practices to ultimately ameliorate the organizational quality performance and innovation performance.